PENGGUNAAN ALAT PERAGA DALAM PEMBELAJARAN MATEMATIKA SMP - Finsensius Yesekiel Naja (Program Studi Pendidikan Matematika, 2018)
This research was aimed to describe the effectiveness of the use of aids in mathematics instruction in SMP, with: 1) compare the mathematics learning achievement of students who were taught using real aids with that of students who were taught using half-real aids.; 2) compare the mathematics learning mastery of the students from both schools categories. This research is a quasi-experiment with pretest-postest design with non-equivalent groups. This research used two experiment groups and two control groups. Population of this research was fifth grade students of state SMP in Detusoko. Stratified random sampling technique was used to select the sample. From the population, the researcher took two schools and every school consisted of two classes as a sample. The total of the sample are 100 people. Data were collected using test. The test were tried out to two groups of students. To compare the mathematics learning achievement of students, data were analyzed by descriptive statistic and inferential statistic by analysis of covariant (? =0.05) and was continued with Tukey-Kramer test (? =0.05), while to compare the mathematics learning mastery of the students, data were analyzed by Chi-Square test. The result of this research showed that: 1) from both schools categories the mathematics learning achievement of students who were taught using real aids is higher than that of students taught using half-real aids; 2) the mathematics learning mastery of high category school students who were taught using real aids is higher than that of high category school students who were taught using half-real aids; 3) the mathematics learning mastery of low category school students who were taught using real aids is not higher than that of low category school students who were taught using half-real aids; 4) from both schools categories the students who were taught using real aids, reach the mathematics learning mastery level, while the students who were taught using half-real aids, do not reach the learning mastery level.